1997
DOI: 10.1021/la9620014
|View full text |Cite
|
Sign up to set email alerts
|

Diamine Immobilization on Silica Gel through the Sol−Gel Process and Increase in the Organic Chain by Using Glutaraldehyde followed by Ethylenediamine

Abstract: The propylethylenediamine moiety was anchored on silica in acid medium by using sol−gel methodology. A sequence of reactions was carried out with glutaraldehyde followed by ethylenediamine in order to increase the organic chain pendant groups covalently bonded to the inorganic support. All synthesized silicas were characterized by carbon and nitrogen elemental analyses, thermogravimetry, differential scanning calorimetry, solid state 13C and 29Si NMR, and calorimetry. These analyses and techniques quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 45 publications
1
39
0
6
Order By: Relevance
“…These processes corresponded to the lost of water, the condensation of the remaining silanol groups, and the organic decomposition in the modified silicas (20,21). From these results, it is observed that the thermal ana lyses show that the bonded phases become less stable as longer alkyl group chains are bonded to the inorganic backbone.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These processes corresponded to the lost of water, the condensation of the remaining silanol groups, and the organic decomposition in the modified silicas (20,21). From these results, it is observed that the thermal ana lyses show that the bonded phases become less stable as longer alkyl group chains are bonded to the inorganic backbone.…”
Section: Resultsmentioning
confidence: 93%
“…These large values, obtained by using the present procedure, are in agreement with the great potentiality of this new matrix to react with silylating agents. To support this argument, a normal chromatographic silica gel has a maximum amount of anchored molecules on the order of 1.5 mmol g −1 , when this same experimental method was employed (21). On the other hand, within the series of organofunctionalization of these matrices at different timers, the organic content remains constant after 48 h of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of both silicas follow the procedure described elsewhere (26), but with some modifications. About 50 g of activated silica was immersed in 100 mL of dry xylene and 20 mL of tmpe was added.…”
Section: Synthesis Of the Organofunctionalized Silicasmentioning
confidence: 99%
“…A potencialidade em aumentar a cadeia do agente sililante pode ser constatada através de um dialdeído, cuja reação controlada em termos estequiométricos, superfície aminada: glutaraldeído, forma facilmente a base de Schiff, a qual pode ser reduzida em etapas posteriores, para seguir uma seqüência de reações para conduzir ao produto final com claro crescimento da cadeia 15 , como mostra a Equação 8. Após a imobilização e redução da dupla ligação, o material possui a capacidade de remover cátions 16 .…”
Section: Sílica Gelunclassified